(untitled) (Experimental biology, 2018)
The aim of the study is to analyze the habitats of barberry species in Kazakhstan at the present time, as well as to establish modern areological characteristics of species and formulation of tasks for the development of research on the genus Berberis L. in the territory of the republic. There are different versions in understanding of species variability Berberis L. in Kazakhstan. Up to 60-th of XX century there were 8 species. To the end of 60-th of XX century the number of species reduced to 6 species. Such opinion is the same with modern. But in different books we see different understanding of species. The objects of our investigations were habitats of Berberis species in Kazakhstan in fundamental taxonomic books. The Electronic Data base of Herbarium of Institute of Botany and Phytointroduction was the object of the investigation as well. Our investigation had shown next. There are 6 species of Berberis L. on Kazakhstan’s territory now. These plants are growing in Kazakhstan in mountains only. Go after specific of species of Berberis in Kazakhstan’s habitat is divided into three parts – north-east, south-east and south.